Does the Exclusion Argument Put Any Pressure on Dualism?. Issue 1 (2nd January 2017) - List, Christian; Stoljar, Daniel
ABSTRACT: The exclusion argument is widely thought to put considerable pressure on dualism, if not to refute it outright. We argue to the contrary that, whether or not their position is ultimately true, dualists have a plausible response. The response focuses on the notion of 'distinctness' that is employed to distinguish between mental and physical properties: if 'distinctness' is understood in one way, the exclusion principle on which the argument rests can be denied by the dualist; if it is understood in another way, the argument is not persuasive.